An Analysis of the Bullwhip Effect in Multi-echelon Hybrid Supply Chain. Issue 13 (2019) - Lin, Wenjin; Ren, He; Peng, Qiyun; Ye, Song; Jiang, Zhibin; Wang, Kangzhou
Abstract: As service is becoming the strategic preference in the manufacturing industry, more and more manufacturing companies provide customers with total solutions or product service system by integrating services into their core product offerings, which is usually implemented in so-called hybrid supply chain. The hybrid supply chain is formed as a chain by multi-echelon manufacturers and service providers who work together to offer product service system to customers. In multi-echelon hybrid supply chain, each echelon customers' response to variable service levels and interaction between inventory and service capacity strategy have a great impact on supply chain instability, which represents an important concern in supply chain research. To tackle this problem, we establish a system dynamics model, by taking the multi-echelon hybrid supply chain for a logistics equipment company in China as an example. Firstly, we analyzed the oscillation characteristics of service flow and product flow. Then, we proposed the performance metrics of bullwhip effect in multi-echelon hybrid supply chain. Finally, based on the model, we found that the bullwhip effect of multi-echelon hybrid supply chain could be smoothened by incorporating forecast smooth factor, control percentage coefficient and order lead time.